Orthodenticle is necessary for survival of a cluster of clonally related dopaminergic neurons in the Drosophila larval and adult brain. - Blanco, J.; Pandey, R.; Wasser, M.; Udolph, G. (Neural Development, 2011)
The dopaminergic (DA) neurons present in the central brain of the Drosophila larva are spatially arranged in stereotyped groups that define clusters of bilaterally symmetrical neurons. These clusters have been classified according to anatomical criteria (position of the cell bodies within the cortex and/or projection pattern of the axonal tracts). However, information pertaining to the developmental biology, such as lineage relationship of clustered DA neurons and differential cell subtype-specific molecular markers and mechanisms of differentiation and/or survival, is currently not available.Using MARCM and twin-spot MARCM techniques together with anti-tyrosine hydroxylase immunoreactivity, we have analyzed the larval central brain DA neurons from a developmental point of view and determined their time of birth, their maturation into a DA neurotransmitter phenotype as well as their lineage relationships. In addition, we have found that the homeodomain containing transcription factor Orthodenticle (Otd) is present in a cluster of clonally related DA neurons in both the larval and adult brain. Taking advantage of the otd hypomorphic mutation ocelliless (oc) and the oc2-Gal4 reporter line, we have studied the involvement of orthodenticle (otd) in the survival and/or cell fate specification of these post-mitotic neurons.Our findings provide evidence of the presence of seven neuroblast lineages responsible for the generation of the larval central brain DA neurons during embryogenesis. otd is expressed in a defined group of clonally related DA neurons from first instar larvae to adulthood, making it possible to establish an identity relationship between the larval DL2a and the adult PPL2 DA clusters. This poses otd as a lineage-specific and differential marker of a subset of clonally related DA neurons. Finally, we show that otd is required in those DA neurons for their survival.